Spring Water Quality Assessment Using Water Quality Index in Shawre Valley- Sulaymaniyah-Iraqi Kurdistan Region - Sara A. Yasin; Alwan Q. Ahmed; Lanja O. Tahir; Rezan S. Ahmed (Zanco Journal of Pure and Applied Sciences, 2023)
The current study was conducted to assess the suitability of springs for drinking purposes in Shawre Valley in Sulaymaiyah Governorate, Kurdistan region of Iraq, using the Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI). Water samples were collected from four springs (Daraban, Mam Xalan, Dolli Shawre, and Sarukani) and analyzed for seventeen physicochemical parameters including Turbidity, Hydrogen Ion Concentration (pH), Electrical Conductivity (EC), Total Dissolved solids (TDS), Total hardness, Calcium (Ca2+), Magnesium (Mg2+), Total Alkalinity, Sodium (Na+), Potassium (K+), Chloride (Cl-), Sulfate (SO42-), Nitrate (NO3-), Nitrite (NO2-), Phosphate (PO43-), Dissolved oxygen (DO), and Biochemical oxygen demand (BOD5) from October 2021 to February 2022. The results of physicochemical parameters indicated that most of the spring’s water samples lie within the permissible limit as compared by WHO for drinking purposes, except for Turbidity, EC, TDS, Total hardness, Mg2+, DO, and BOD5, which exceed the standard values at Daraban, Mam Xalan, and Dolli Shawre springs and are considered unfit for drinking consumption. The results showed that the calculated CCME WOI values ranged from 74.00 to 88.45. Generally, the overall water quality index showed that Mam Xalan spring of 64.00 falls under the "Marginal" category, while Daraban and Dolli Shawre of 65.00 and 78.45 respectively fall under "Fair" quality. Furthermore, Sarukani spring of 88.079 falls under "Good" quality. On the basis of WQI results, most of the spring water samples fall under the Fair and Marginal categories, indicating that they require proper treatment for drinking purposes.